Introduction (Scottish Historical and Archaeological Internet Reports, 2003)
This section describes the background to the project and the location of the archive. The intention was to determine how similar the Capo long barrow is the nearby Dalladies monument and to assess the extent of the damage caused by rabbit burrowing and tree-roots.